2012 Sixth Asia Modelling Symposium 2012
DOI: 10.1109/ams.2012.40
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Signal-to-Noise Ratio Estimator with Adaptive Modulation

Abstract: Adaptive modulation techniques in wireless communications are paramount technologies designed to thrive in fading and noisy environments. Methods as such require an accurate estimate of the channel condition at the receivers' end in order for the transmitter to adapt appropriately. With that in mind, a communication link which changes the degree of modulation scheme according to the estimated signal-to-noise ratio (SNR) values is proposed. Hence, the objective of the system is to achieve acceptable quality in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…It can pair with adaptive modulation and coding schemes to overcome the uncertainties in time-varying conditions. Other applications of SNR information include: information in tactical applications, jamming analysis, and electronic surveillance system [15].…”
Section: Performance Of M-ary Psk With Coding Adaptationmentioning
confidence: 99%
“…It can pair with adaptive modulation and coding schemes to overcome the uncertainties in time-varying conditions. Other applications of SNR information include: information in tactical applications, jamming analysis, and electronic surveillance system [15].…”
Section: Performance Of M-ary Psk With Coding Adaptationmentioning
confidence: 99%
“…The overall performance of satellite communication network is generally presented in terms of carrier power above the noise level. The carrier to noise ratio (C/N) of any radio frequency (RF) signal and the bit energy to noise density (Eb/No) for digital system are important performance parameters to consider for optimal data rate [10]. Studies have shown that link availability above the threshold is critical for quality of service in terms carrier power above the system noise level [11].…”
Section: Introductionmentioning
confidence: 99%
“…In [ 12 ], the authors suggested preamble-aided channel quality estimation (i.e., DA-SNR) as a metric for channel adaptation to improve the link quality under dynamic interference of WSN. In [ 13 ], the authors explored the scheme by evaluation DA-SNR to select the modulation order for the transmitter; and Hanzo and Torabi et al [ 14 , 15 ] optimized the switching levels of DA-SNR to improve the throughput performance. However, DA-SNR-AM research mostly focuses on DA-SNR estimation and switching level optimization for certain special channels, such as additive white Gaussian noise (AWGN) and Rayleigh fading channels, which cannot provide the general model for NLOS propagation scenario in a realistic WSN.…”
Section: Introductionmentioning
confidence: 99%